Entrepreneurship Education as an Investment in Human Resources for Long-Term Economic Development - Sachrir, Muh Irshan (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2025)
Entrepreneurship education plays a strategic role in developing human resources (HR) that are adaptive, creative, and competitive, making it an important instrument for long-term economic development. This article aims to analyze the interrelation between entrepreneurship education, HR investment, and long-term economic development through a literature review approach. Research data were collected using documentation techniques, by examining indexed international journal articles, academic books, and oficial reports from international institutions. The findings indicate that entrepreneurship education serves as a foundation for building entrepreneurial competencies, which subsequently encourages greater investment in HR through education, training, health, and financial literacy. Such investment produces competitive, productive, and adaptive HR, thereby contributing to sustainable long-term economic development. The novelty of this study lies in the development of an integrative conceptual framework that connects entrepreneurship education, HR investment, and long-term economic development in the context of developing countries.